Erros de medicação antibacteriana e a interface com a segurança do paciente - Pereira, Francisco Gilberto Fernandes (2015)
The security related to the medication system has been recent research objec t, mainly in relation to antibacterial that have high pharmacological specificity and may have impaired its action to the detriment of errors associated with the phases of preparation and administration. Thus, the study aimed to analyz e the behavioral and environmental factors involved in the occurrence of errors during the stages of antibacterial administration preparation. This is an observational, exploratory and cross - sectional study, quantitative, conducted from August to December 2014 in the Sentinel Network Hospital in Fortaleza. The sample comprised 44% of the antibiotic dose of medical clinics A and B, 108 and 157, respectively. Data collection took place in two phases: the first to characterize the occupational profile member o f the nursing staff; and the second to identify the adaptations and behavioral and environmental inadequacies in the phases of preparation and administration. Data were organized in tables and analyzed using descriptive and analytical statistics. All bioet hical principles were respected, as approved by the Research Ethics Committee of the Federal University of Ceará, protocol number 660 897. The results allowed to perform the following inferences: the completion of the preparation and administration of anti bacterial was performed by nursing technicians (100%), predominantly female, aged 31 - 40 years who have completed training between the last ten to 20 years and working in the area for a similar period, however, there are less than ten years in the instituti on where the research took place. On the influence of environmental factors we found that during the preparation was inadequate at 136 observations on cleanliness and variable 187 within the organization. The size for the preparation was inadequate in the Medical Clinic A (3,8m2), and the items lighting, temperature and noise were extremely oscillating in three shifts and two clinics, with average generally higher than recommended. As regards the behavioral variables observed: producing sources of interrupt s in 145 doses during preparation, and however, were not statistically significant to increase the time of preparation of antibiotics (p = 0.776). There was a higher frequency of non - compliances respectively in clinics A and B on the items: Prescription us e behavior 86 (79.6%) and 157 (100%); confirmation of the patient's name 68 (62.9%) and 142 (90.4%); and monitoring 84 (77.7%) and 82 (52.2%). Already Medical Clinic B had higher compliance rates in infusion time control of 84 (53.5%) and immediate check 9 3 (59.2%). Contributing factor to increase the chances of drug interaction was the absence of guidelines with information about the drug (p = 0.003). The main error category was the dose found error (157). Since the most commonly used antibiotic piperacill in + tazobactam was 51 doses